Pushing the Boundaries of Tortious Liabilities for Genetic Contamination of Genetically Modified (GM) Crops: The Challenges and Regulatory Measures - Siti Hafsyah Idris, Noraiza Abdul Rahman (International Journal of Advanced Science and Technology, 2020)
Genetic contamination (cross-pollination from Genetically Modified (GM) crops) highlights the immense challenge of controlling GM crop technologies. While only is genetic pollination inevitable, insufficient legislation often refuses to keep seed producers responsible for the potential harm and eventually puts the blame on farmers who have become victims of pollution. Corporations will pursue civil measures against farmers who cultivate transgenic crops without the authorisation of corporations. A farmer who is the victim of genetic manipulation may be found accountable to the company that produced the GM crops, irrespective of the individual that commits the violating actions. When GM crops cross-pollinate on adjacent fields with sustainable or traditional crops, the absence of a legal system may compel farmers to fight in court. This can cause drastic economic losses for farmers facing export-market rejection that prohibits GM crops. Organic farmers with GM contamination, could lose their organic certification and their organic crop premium. When consumer demands for non-GM crops increases, farmers explore ways to diversify into non-GM crops markets that pay higher prices. Yet industries’ failure to adequately segregate GM crops from traditional varieties tends to challenge these producers. Regulatory measures need to be adopted and implemented to shield farmers from GM crop liability issues, primarily to protect farmers who cultivate traditional crops from contamination of GM crops. Therefore, stringent pollution regulation is important to protect non-GM farmers against biotechnology corporations who establish and hold intellectual property rights in the pollution-causing GM seed.